Cost of benign versus oncologic colon resection among fee‐for‐service Medicare enrollees. Issue 2 (27th May 2019) - Hughes, Byron D.; Hancock, Kevin J.; Shan, Yong; Thakker, Ravi A.; Maharsi, Safa; Tyler, Douglas S.; Mehta, Hemalkumar B.; Senagore, Anthony J.
Abstract: Background and Objectives: Reimbursement for colonic pathology by the Centers for Medicare and Medicaid Services (CMS) are grouped in the Medicare Severity‐Diagnosis Related Groups (MS‐DRG). With limited available data, we sought to compare the relative impact of malignant vs benign colonic pathology on reimbursement under the MS‐DRG system. Methods: We used 5% national Medicare data from 2011 to 2014. Patients were classified as having benign disease or malignancy. Descriptive statistics and multivariate regression analysis were used to evaluate the surgical approach and health resource utilization. Results: Of 10 928 patients, most were Non‐Hispanic White women. The majority underwent open colectomy in both cohorts ( P < .001). Colectomy for benign disease was associated with higher total charges ( P < .001) and a longer length of stay ( P = .0002). Despite higher charges, payments were not significantly different between the cohorts ( P = .434). Both inpatient mortality and discharge to a rehab facility were higher in the oncologic group ( P < .001). Conclusion: Payment methodology for colectomy under the CMS MS‐DRG system does not appear to accurately reflect the episode cost of care. The data suggest that inpatient costs are not fully compensated. A transition to value‐based payments with expanded episode duration will require a better understanding of unique costs before adoption.